O (falso) problema da culpabilidade penal: sobre as possibilidades de diálogo entre direito penal e neurociências - Isadora Eller Freitas de Alencar Miranda (2018)
As understood in the context of the theory of crime, the word "culpability" corresponds to one of the three elements that compose concept of "crime". In this sense, the institute represents both the criteria of personal responsibility of an agent established by a system and the very element of justification for the existence of the model. For the Brazilian criminal law, which is based in the finalist theory, as proposed by Hans Welzel, both criteria are based on the idea that agents dispose of moral freedom, that is, on their free will. However, the validity of this concept, discussed throughout the history of philosophy and criminal law, is confronted, nowadays, by the neurosciences, which reflect a materialist view of the brain and the human behavior. Considering the above, this work will discuss the relationship between the concepts of criminal culpability and free will, addressed by the Classical School and the Positive School of Criminology, as well as, posteriorly, by the theories of crime. In a second moment, it will be explained, in a broader perspective, what are the neurosciences, and the implications of this field of research for the formulation of the criteria of criminal responsibility and the justification of criminal law. In this opportunity, the incompatibilities between the presuppositions of the finalist theory and the discoveries from the neuroscientific research will be stressed. As an alternative, there will be presented some already existent criminal models that, by diverting from an essentially libertarian grounding, could remain valid, even if the conclusions of the neurosciences (under a deterministic perspective) are true, namely: the penal guaranteeism of Luigi Ferrajoli; the teleological functionalism of Claus Roxin and the systemic functionalism of Günther Jakobs.